2020
DOI: 10.1111/cod.13535
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of life (QoL) of patients with dermatitis and the impact of patch testing on QoL: A study of 519 patients diagnosed with dermatitis

Abstract: BackgroundDermatitis can impair the quality of life (QoL) of patients. Knowledge of the QoL‐associated factors and the impact of patch testing on QoL is limited.ObjectivesTo identify demographic and clinical factors affecting QoL, and to measure the impact of patch testing on QoL of dermatitis patients.MethodsThe data and Dermatology Life Quality Index (DLQI) questionnaires of 519 dermatitis patients were analyzed. Of these, 107 underwent patch testing and completed the questionnaires two times (once before te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…In a study done by Waranya Boonchai et al . [ 17 ] mean DLQI 9.5, which was less as compared to our study.…”
Section: Discussioncontrasting
confidence: 89%
“…In a study done by Waranya Boonchai et al . [ 17 ] mean DLQI 9.5, which was less as compared to our study.…”
Section: Discussioncontrasting
confidence: 89%
“…In these studies, FD has been associated with low quality of life in AD patients especially within the areas of social activities and embarrassment. [37][38][39] Both of these areas are mentioned by the patients in our nonvalidated questionnaire as the primary cause of limiting their daily life.…”
Section: Skin Test Study With Natural Ingredientsmentioning
confidence: 99%
“…Furthermore, these clinical visits would probably have led to improvement of the patients' knowledge as well as improved management of eczema and the skin barrier. Previous studies have reported an improvement in QoL in patients after patch testing 22 . It has been shown that QoL improves over time after patch testing both at a shorter 8–12 and a longer follow‐up period 13 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported an improvement in QoL in patients after patch testing. 22 It has been shown that QoL improves over time after patch testing both at a shorter 8 , 9 , 10 , 11 , 12 and a longer follow‐up period. 13 An improvement in life quality after patch test could be seen in patients with a positive patch test as well as patients with no contact allergies.…”
Section: Discussionmentioning
confidence: 99%